Respuesta :
Answer:
4 (-1-11) + 2 (17)
Answer 2 is -14
Step-by-step explanation:
Expressions can be factorized by taking their greatest common factor (GCF)
- The factored expression that represents the sum is: [tex]\mathbf{4(-1 - 11)+ 2(17) }[/tex]
- Her answer is -14
From the given table, the sum can be represented as:
[tex]\mathbf{Sum = -11 + 17 -1 -1 -1 -1 -11 + 17 -11 - 11}[/tex]
Rewrite as:
[tex]\mathbf{Sum = -11 -11 -11 - 11 -1 -1 -1 -1 + 17 + 17}[/tex]
Express as sum of products
[tex]\mathbf{Sum = -11 \times 4 -1 \times 4 + 17 \times 2}[/tex]
Factorize
[tex]\mathbf{Sum = 4(-1 - 11)+ 2(17) }[/tex]
So, the factored expression that represents the sum is: [tex]\mathbf{4(-1 - 11)+ 2(17) }[/tex]
The answer is calculated as follows
[tex]\mathbf{Sum = 4(-1 - 11)+ 2(17) }[/tex]
[tex]\mathbf{Sum = 4(-12)+ 2(17) }[/tex]
[tex]\mathbf{Sum = -48+ 34 }[/tex]
[tex]\mathbf{Sum = -14}[/tex]
Her answer is -14
Read more about factorization at:
https://brainly.com/question/19386208